The Does hepatic-jejunostomy favour subsequent ulcero-peptic gastroduodenal disease? Estudio retrospectivo de 62 hepaticoyeyunostomías por lesiones histológicamente benignas de la vía biliar - Colet, Andrés; González, Jorge; di Donna, Bruno; Estefan, Alberto; Praderi, Raúl (Cirugía del Uruguay, 1984)
Authors carried out a retrospectiva study of 62 cases of hepatic-jejunal anastomosis performed at Surgical Clinic "3" for the treatment of histologically benign le• s o the biJiary duct, trying to establish the incidence o gastroduodenal peptic ulcer in the postoperative immediate evolution, in the short and the long run.